Synthesis and Characterization of Triphenylamine Appended Porphyrins and their Intramolecular Energy Transfer - Bai, M.; Ma, Q.; Song, R.; Meng, F. (Asian Journal of Chemistry, 2014)
A series of 5,10,15-triphenyl-20-(triphenylamino)porphyrinato zinc(II) (ZnTPP(TPA)1 (1), 5-phenyl-10,15,20-tris(triphenylamino)-porphyrinato zinc(II) (ZnTPP(TPA)3 (2) and 5,10,15,20-tris(triphenylamino)porphyrinato zinc(II) (ZnTPP(TPA)4 (3) were synthesized using 4-(N,N-diphenylamino)benzaldehyde, benzaldehyde and pyrrole as starting materials. All porphyrins were characterized with various spectroscopic methods, MALDI-TOF mass, UV-vis, 1H NMR and 2D COSY spectroscopy. The structure of 5,10,15-triphenyl-20-(triphenylamino)porphyrin [H2TPP(TPA)] was also established by X-ray diffraction analyses. The absorption and emission spectra indicate that there are strong interactions between zinc porphyrin core and triarylamine at ground states. Excited energy transfer from triphenylamine to porphyrin was proved by the fluorescence spectra.